2014
DOI: 10.1016/j.amepre.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity Among U.S. Workers and Associations with Occupational Factors

Abstract: Work-related factors may contribute to the high prevalence of obesity in the U.S. working population. Public health professionals and employers should consider workplace interventions that target organization-level factors, such as scheduling and prevention of workplace hostility, along with individual-level factors such as diet and exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
147
4
12

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(186 citation statements)
references
References 35 publications
23
147
4
12
Order By: Relevance
“…In particular, the analysis by categories of subjects has put into evidence the high frequency of obesity among transportation workers, a finding in line with a recently published study investigating obesity among professional drivers in Italy [29]. Similarly, an even higher prevalence of obesity in workers employed in public administration, was also revealed in the study by Luckhaupt et al [24]. After adjusting for the interaction of working contract and > 40 h/week, however, a number of categories showed a lower risk of obesity, in particular, this phenomenon was found in workers employed in manufacturing industry, construction, financial, real estate, commerce, bar and catering services.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In particular, the analysis by categories of subjects has put into evidence the high frequency of obesity among transportation workers, a finding in line with a recently published study investigating obesity among professional drivers in Italy [29]. Similarly, an even higher prevalence of obesity in workers employed in public administration, was also revealed in the study by Luckhaupt et al [24]. After adjusting for the interaction of working contract and > 40 h/week, however, a number of categories showed a lower risk of obesity, in particular, this phenomenon was found in workers employed in manufacturing industry, construction, financial, real estate, commerce, bar and catering services.…”
Section: Discussionsupporting
confidence: 76%
“…The results are in line with a recent study from the literature that found significant associations between long work hours, hostile work environments, and obesity among a nationally representative sample of U.S. workers. However, in Italy, we have found a lower prevalence of obesity (9.1%) in the working population, with respect to the USA, where 27.7% of workers are obese [24].…”
Section: Resultsmentioning
confidence: 68%
“…No que se refere à influência do ambiente, resultados recentes indicam sua relação tanto sobre as práticas alimentares quanto com a disposição com atividades físicas 6 . Ademais, evidencia-se, na literatura, a associação entre obesidade e ambientes de trabalho com características hostis e longas jornadas 7,8 .…”
Section: Objectiveunclassified
“…Luckhaupt et al 7 , em um inquérito de saúde, detectaram maior prevalência de obesidade (36,3%) em funcionários da administração pública nos Estados Unidos da América, quando comparada à prevalência na população total de trabalhadores estudados (27,7%) naquele país e na população geral (32,6%) 1 . Nessa direção, este artigo objetivou identificar se características sociodemográficas, hábitos alimentares, situação de saúde e condições de trabalho estavam relacionadas ao excesso de peso em um grupo de servidores e empregados públicos municipais.…”
Section: A Total Of 444% Of the Participants (N=4893) Had Excess Weunclassified
See 1 more Smart Citation